2013
DOI: 10.1186/1471-2148-13-141
|View full text |Cite
|
Sign up to set email alerts
|

A phylogenetic analysis of the grape genus (Vitis L.) reveals broad reticulation and concurrent diversification during neogene and quaternary climate change

Abstract: BackgroundGrapes are one of the most economically important fruit crops. There are about 60 species in the genus Vitis. The phylogenetic relationships among these species are of keen interest for the conservation and use of this germplasm. We selected 309 accessions from 48 Vitis species,varieties, and outgroups, examined ~11 kb (~3.4 Mb total) of aligned nuclear DNA sequences from 27 unlinked genes in a phylogenetic context, and estimated divergence times based on fossil calibrations.ResultsVitis formed a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
169
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(195 citation statements)
references
References 110 publications
23
169
3
Order By: Relevance
“…2) representing genetic relationship between accessions and between species in this study are very similar to those in our previous study estimated by other algorithms (Wan et al 2013). …”
Section: Comprehensive Interpretation Of Genetic Relationships Of Vitmentioning
confidence: 58%
See 4 more Smart Citations
“…2) representing genetic relationship between accessions and between species in this study are very similar to those in our previous study estimated by other algorithms (Wan et al 2013). …”
Section: Comprehensive Interpretation Of Genetic Relationships Of Vitmentioning
confidence: 58%
“…High nucleotide diversity (Table S9) and high CV value of nucleotide diversity (Table S53) in most Vitis species suggested high genetic variability in these species. Our previous study confirmed broad hybridization among species in the evolutionary history of Vitis (Wan et al 2013). In this case, the phylogenetic species concept may be unsuitable as suggested by López-Pujol et al (2012).…”
Section: Comprehensive Interpretation Of Genetic Diversity and Genetimentioning
confidence: 63%
See 3 more Smart Citations